2021
DOI: 10.3389/fonc.2021.647546
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Resectable N2 in NSCLC: A Single Center Experience and Review of the SEER Database

Abstract: BackgroundNon-small cell lung carcinoma (NSCLC) with ipsilateral and/or subcarinal mediastinal lymphatic spread (N2) is a heterogeneous disease. The role of surgical resection in patients with N2 NSCLC remains controversial and no survival-based definition of “resectable N2” exists. The purpose of this study is to evaluate the factors that potentially affect the survival of N2 NSCLC patients who receive surgical resection and to define “resectable N2” based on the survival benefits.MethodsData from the open Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
(34 reference statements)
2
3
0
Order By: Relevance
“…Similar to a previous study ( 17 ), we conducted univariable and multivariable analysis and found that N2 patients who received pneumonectomy, who were diagnosed in 2010–2015, who were younger, who were female, with a non-white race, with a marital status other than separated/divorced/widowed, with upper lobe disease, with adenocarcinoma, with a higher differentiated degree, with a lower T classification, and who received chemotherapy or/and radiotherapy were significantly associated with better long-term outcome. Chemotherapy and radiotherapy have been proven to be effective for NSCLC patients.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similar to a previous study ( 17 ), we conducted univariable and multivariable analysis and found that N2 patients who received pneumonectomy, who were diagnosed in 2010–2015, who were younger, who were female, with a non-white race, with a marital status other than separated/divorced/widowed, with upper lobe disease, with adenocarcinoma, with a higher differentiated degree, with a lower T classification, and who received chemotherapy or/and radiotherapy were significantly associated with better long-term outcome. Chemotherapy and radiotherapy have been proven to be effective for NSCLC patients.…”
Section: Discussionsupporting
confidence: 86%
“…analyzed 4,267 N2 patients in the SEER database and developed a nomogram for prognosis prediction. They demonstrated that a multidisciplinary team should decide whether or not to perform surgical resection in N2 patients ( 17 ). For N2 patients with a central giant mass or tumor involving the main bronchus or large blood vessels, pneumonectomy is the primary surgical technique for R0 resection, usually accompanied by neoadjuvant chemoradiotherapy or induction therapy ( 5 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas in this study radiotherapy was found to shorten survival time in NSCLC patients with survival time >14 months. Another study also found radiotherapy before or after surgery was associated with a higher risk of death, the possible reason for this may be the large proportion of stage III and IV patients treated with radiotherapy, which affected the prognosis (27). In this study, it was also found that the proportion of distant stage in the patients with radiotherapy group (63.88%) was higher than that in the non-radiotherapy group (49.57%).…”
Section: Discussionsupporting
confidence: 61%
“…The cancer-related data in the SEER Program were obtained from 18 population-based registries, covering approximately 26% of the US population. Compared with any single institution, the SEER database encompasses much more population-level cancer data based on the largest sample size worldwide (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%